A Semantic Analysis of the Root [س-ل-م] and Its Derivatives in the Qur'an: A Case Study of the Indonesian Ministry of Religious Affairs Qur'an Translation - Ramadhan, Rezky; Haeruddin, Haeruddin; Baso, Yusring Sanusi; Andi, Agussalim (Journal of Language and Literature Studies, 2026)
In the Qur'an, changes in morphological patterns (wazan) not only produce grammatical variations, but also give birth to differences in meaning. One of the most productive roots in the Qur'an is the root [س-ل-م], which gives birth to various derivations. The word سلم is often interpreted in a limited way as "peace" or "Islam". This study aims to identify all derivations  of the root [س-ل-م], classify its morphological form, and analyze its core meaning and semantic development in the translation of the Qur'an of the Ministry of Religion of the Republic of Indonesia. This study uses a qualitative-descriptive design with a morpho-semantic approach. Data were collected through a documentation technique by tracing all Qur'anic verses containing derivatives of the root, then analyzed through the stages of identification, morphological classification, determination of core meaning, and contextual analysis. The results showed that the root س-ل-م (s-l-m) appeared 140 times with 16 derivative forms, dominated by the nominal form (112 data) rather than the verbal (28 data). Semantically, these roots form a network of meanings that include existential salvation, spiritual surrender, theological systems (Islam), collective identity (Muslim), social peace, and cosmic surrender. This study confirms that the concept of salvation in the Qur'an is multidimensional and linguistically structured.